People's Motives Toward Bone Fracture Alternative Treatment in District of Bandung Barat - Fatma Sjoraida, Diah; Novianti, Evi; Rizal, Edwin; Sri Rezeki, Diah (International Journal of Engineering and Technology, 2018)
The purpose of this study is to determine the community motive towards an alternative treatment of bone fractures in the district of West Bandung. Today, alternative treatment, especially fracture bone treatment is still popular with the societies, whereas technology and science in the medical world are growing very rapidly. The research method used is qualitative with phenomenology approach. The results of the study show some motives that are the reasons for choosing alternative treatment, among others: [1] Economic motives. The cost of alternative treatment of fractures is fairly cheap because it is not emphasized on a certain amount of cost. [2] Social motives. Believe in the neighbor's experience or experience of the public figures who have done the alternative treatment. [3] Psychological motives. Feel safe and not afraid when doing alternative treatments.Â Â